Visualization Techniques Through Search Interfaces in Learning Object Repositories - Gaona García, Paulo Alonso; Fermoso García, Ana; Sánchez Alonso, Salvador; Gaona García, Elvis Eduardo (Tecnura, 2014)
In this paper, it is presented a study to evaluate and compare the effectiveness of eight different interfaces based on visualization techniques to carry out searching digital resources according to knowledge area and knowledge representation scheme. The navigation structure is based on hierarchical taxonomic representation through the use of Art and Architecture Thesaurus (AAT). It was adopted principles of Human Computer Interaction (HCI) for the development of search interfaces through information visualization techniques. Finally, it will be presented preliminary results in order to evaluate the most representative aspects to carry out the development of visual search interfaces of learning objects in digital repositories, according to principles of visualization techniques and hierarchic taxonomic classification.